Improving educational facilities at vocational high schools based on regional public service agency: A literature study - Arin Ika Puspitaningsih; Nurul Ulfatin; Syamsul Hadi; Rody Putra Sartika (Jurnal Pendidikan Vokasi, 2023)
This research aims to provide information about Vocational High Schools (VHS) based on the Regional Public Service Agency (RPSA). This descriptive qualitative research uses a literature study approach, which includes several activities related to library data collection methods, reading, recording, and processing research materials. Meanwhile, content analysis is the analytical approach used. The findings of this study reveal various aspects of the management of VHS based on the regional public service agency: definition, benefits, objectives, requirements towards VHS-RPSA, and organizational structure. The management of VHS-RPSA is not for financial gain but to satisfy customers (students and communities) by providing autonomy in handling finances towards school independence, which has several benefits, such as autonomy in financial planning patterns, improved human resources, improved learning, improved facilities and infrastructure, strengthened character education, and improved cooperation. This research enhances the understanding of VHS management within the RPSA framework, contributes to education governance and public service administration to improve the quality of VHS education, and paves the way for future research.